2022
DOI: 10.1093/g3journal/jkac034
|View full text |Cite
|
Sign up to set email alerts
|

Genome assembly of the Australian black tiger shrimp (Penaeus monodon) reveals a novel fragmented IHHNV EVE sequence

Abstract: Shrimp are a valuable aquaculture species globally; however, disease remains a major hindrance to shrimp aquaculture sustainability and growth. Mechanisms mediated by endogenous viral elements (EVEs) have been proposed as a means by which shrimp that encounter a new virus start to accommodate rather than succumb to infection over time. However, evidence on the nature of such EVEs and how they mediate viral accommodation is limited. More extensive genomic data on Penaeid shrimp from different geographical locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 76 publications
(114 reference statements)
0
8
0
Order By: Relevance
“…Huerlimann et al [ 15 ] give a detailed analyses of the EVE cluster found on SG97 of their Australian P. monodon specimen plus a detailed comparison of it to the two EVE clusters that they (like us) discovered in PC35 of the Thai P. monodon WGS. Thus, those interested the detailed comparison should consult the Australian publication.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Huerlimann et al [ 15 ] give a detailed analyses of the EVE cluster found on SG97 of their Australian P. monodon specimen plus a detailed comparison of it to the two EVE clusters that they (like us) discovered in PC35 of the Thai P. monodon WGS. Thus, those interested the detailed comparison should consult the Australian publication.…”
Section: Resultsmentioning
confidence: 98%
“…A recent publication [ 15 ] using DNA extracted from an Australian P. monodon specimen for genome analysis revealed one EVE cluster in their Scaffold group 97 (SG97) with high identity to GenBank EU675312 (i.e., the Australian version of IHHNV-A with 99% sequence identity to DQ228358). Given the information from our earlier publication and from the work reported herein and from the Australian publication, it is likely that the continuous sequence records for DQ228358 and EU675312 at GenBank are assembly artifacts, and that they were obtained from fragmented and scrambled target sequences that had sufficient overlap to result in their assembly into single linear sequences when using the sequence of infectious IHHNV (GenBank record AF218266) as a reference [ 3 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…We now know that the sequences of the WSSV contigs are very likely an artificial result of the sequence assembly process that uses overlapping small-read sequences assembled against a reference sequence, rather than an actual contiguous sequence in the target genome. This was clearly revealed for EVE of the shrimp virus IHHNV in full shrimp genome sequences developed using long-read technology (Huerlimann et al, 2022; Taengchaiyaphum et al, 2022). The EVE fragments of the IHHNV genome occurred in clusters scrambled (in location and reading direction), some with overlapping sequences that resulted in a cumulative sum of IHHNV-EVE sequence lengths that exceeded the whole IHHNV genome length.…”
Section: Resultsmentioning
confidence: 93%
“…It has recently been revealed that shrimp EVE may also give rise to cvcDNA that can be selectively isolated and sequenced as a means of screening for EVE in shrimp breeding stocks (Taengchaiyaphum et al, 2021). Based on data from whole genome sequencing of the giant tiger shrimp Penaeus monodon , it has been shown that EVE occur as fragments together with host transposable element sequences in host shrimp piRNA-gene-like clusters bracketed by linear repeats (Huerlimann et al, 2022; Taengchaiyaphum et al, 2022). The viral genome fragments in these clusters are scrambled in terms of reading direction and original genome position and may also redundantly overlap when mapped to the target virus genome.…”
Section: Introductionmentioning
confidence: 99%
“…The high percentage of repetitive sequences and the difficulty of DNA manipulation due to the large amount of mucopolysaccharides and phosphatases were the main reasons for the delay in sequencing and assembling the shrimp genome until 2019 [73,74]. Before the application of third-generation long-reads sequencing technology, many attempts to assemble the shrimp genome with short sequencing reads resulted in highly fragmented assemblies, illustrating the repeatability and complexity of the shrimp genome [1,[74][75][76]. Long-reads sequencing using the PacBio or Nanopore platforms to sequence shrimp DNA has effectively solved the problem of fragmented genome assembly.…”
Section: Genome Assembly At Chromosome Levelmentioning
confidence: 99%